Functional analysis of enhancer elements regulating the expression of the Drosophila homeodomain transcription factor DRx by gene targeting. - Klöppel, C.; Hildebrandt, K.; Kolb, D.; Fürst, N.; Bley, I.; Karlowatz, R.J.; Walldorf, U. (Hereditas, 2021)
The Drosophila brain is an ideal model system to study stem cells, here called neuroblasts, and the generation of neural lineages. Many transcriptional activators are involved in formation of the brain during the development of Drosophila melanogaster. The transcription factor Drosophila Retinal homeobox (DRx), a member of the 57B homeobox gene cluster, is also one of these factors for brain development. In this study a detailed expression analysis of DRx in different developmental stages was conducted. We show that DRx is expressed in the embryonic brain in the protocerebrum, in the larval brain in the DM and DL lineages, the medulla and the lobula complex and in the central complex of the adult brain. We generated a DRx enhancer trap strain by gene targeting and reintegration of Gal4, which mimics the endogenous expression of DRx. With the help of eight existing enhancer-Gal4 strains and one made by our group, we mapped various enhancers necessary for the expression of DRx during all stages of brain development from the embryo to the adult. We made an analysis of some larger enhancer regions by gene targeting. Deletion of three of these enhancers showing the most prominent expression patterns in the brain resulted in specific temporal and spatial loss of DRx expression in defined brain structures. Our data show that DRx is expressed in specific neuroblasts and defined neural lineages and suggest that DRx is another important factor for Drosophila brain development.